Implications of urbanisation for Turkey. The case of Istanbul - Keles, R (Springer, 2004)
Istambul is the major city of a rapidly urbanising country, Turkey. Physical, environmental, economic and socio-cultural problems facing the city are described and analysed in this chapter, with special emphasis on the local and national impact of the policies to be implemented. An attempt is also made to see how future developments in the world in general and in the region in particular will affect the quality of the environment and urban management. It seems almost certain that unless the present rate of population growth is curbed in the coming decades, the hopes for sustainable development may just remain on paper.
NATO Advanced Research Workshop on Environmental Challenges in the Mediterranean 2000-2050 -- OCT 02-05, 2002 -- Madrid, SPAIN